Certain geometric properties of generalized Bessel-Maitland function - SONI, Amit; BANSAL, Deepak (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In the present study, we first introduce Generalized Bessel-Maitland function and then derive sufficient conditions under which the Generalized Bessel-Maitland function have geometric properties like univalency, starlikeness and convexity in the open unit disk. Mathematics Subject Classification (2010): 30C45. Received 05 March 2021; Accepted 22 June 2021. Published Online: 2023-12-11 Published Print: 2023-12-30